Comparative Genomic Analysis Reveals Organization, Function and Evolution of ars Genes in Pantoea spp. - Wang, Liying; Wang, Jin; Jing, Chuanyong (Frontiers in Microbiology, 2017)
Numerous genes are involved in various strategies to resist toxic arsenic (As). However, the As resistance strategy in genus Pantoea is poorly understood. In this study, a comparative genome analysis of 23 Pantoea genomes was conducted. Two vertical genetic arsC-like genes without any contribution to As resistance were found to exist in the 23 Pantoea strains. Besides the two arsC-like genes, As resistance gene clusters arsRBC or arsRBCH were found in 15 Pantoea genomes. These ars clusters were found to be acquired by horizontal gene transfer (HGT) from sources related to Franconibacter helveticus, Serratia marcescens, and Citrobacter freundii. During the history of evolution, the ars clusters were acquired more than once in some species, and were lost in some strains, producing strains without As resistance capability. This study revealed the organization, distribution and the complex evolutionary history of As resistance genes in Pantoea spp.. The insights gained in this study improved our understanding on the As resistance strategy of Pantoea spp. and its roles in the biogeochemical cycling of As.